A Note on the Macroeconomic Assumptions of International Financial Management - Giddy, Ian H. (Journal of Financial and Quantitative Analysis, 1977)
Ian H. Giddy, A Note on the Macroeconomic Assumptions of International Financial Management, The Journal of Financial and Quantitative Analysis, Vol. 12, No. 4, Proceedings of the 1977 Western Finance Association Meeting (Nov., 1977), pp. 601-605